FAKTOR-FAKTOR YANG MEMENGARUHI POLA KONSUMSI IKAN RUMAH TANGGA NELAYAN DI KABUPATEN BURU SELATAN - Rahma Amaliyah Borut; Yolanda M T N Apituley; Johanis Hiariey; Dionisius Bawole (Pattimura University, 2022)
Masnana is one of the villages in the coastal area of South Buru Regency where most of the residents are fishermen. The community often face various life problems, such as limited capital and irregular and unpredictable climate that affects production. This condition affects their income level and results in an imbalance in the consumption pattern. The aims of this study: 1) Describe the fish consumption patterns of fishermen's households in Masnana Village, South Buru Regency, 2) Analyze the factors that influence the level of fish consumption of fishermen's households in Masnana Village, South Buru Regency. The basic method of this research is a survey and the sample is taken by exhaustive sampling method. The data were analyzed qualitatively descriptively and quantitatively using multiple linear regression analysis. The results showed that fisherman households in Masnana Village consumed varying amounts of fish every day. The highest level of fish consumption is greater than 1000 grams (1 kg) per day with a household of 5-6 people, while the lowest level of fish consumption is less than 300 grams (0.03 kg) per day with a household of 2 people. If calculated per year, the lowest level of fish consumption is 34 kg/capita/year and the highest is 66 kg/capita/year. Thus the level of fish consumption in some fishing households in Masnana Village has exceeded the average fish needs of the Indonesian people and some have not. The factors that influence the fish consumption patterns of fishermen's households in Masnana Village are household income and the number of household members